Electrodeposition of nickel plates on copper substrates using PC y PRC (2007)
Electrodeposition processes using direct current (DC) require the use of additives to control deposit structure and properties as well as current distribution. The Pulse Current (PC) and Pulse Reverse Current (PRC) techniques improve the properties of deposits based on an appropriate selection of the parameters involved. This research evaluates the influence of cathodic time (ton), anodic time (trev), relaxation time (toff), and voltage on the resistance to corrosion of nickel deposits using the PC and PRC techniques. Test were conducted in a dynamic manner, employing a rotating system with Watt’s solutions as the electrolyte and copper substrate electrodeposited on zamak as cathodes. Measurement of the grain size was conducted using Atomic Force Microscopy. Protection level against corrosion was evaluated by polarization curves and Electrochemical Impedance Spectroscopy. Important results include the formation of uniform deposits showing fine grain and excellent protection against corrosion.